2011
DOI: 10.1088/0022-3727/44/18/185205
|View full text |Cite
|
Sign up to set email alerts
|

Three-dimensional modelling of arc behaviour and gas shield quality in tandem gas–metal arc welding using anti-phase pulse synchronization

Abstract: The paper presents a transient three-dimensional model of an anti-phase-synchronized pulsed tandem gasmetal arc welding process, which is used to analyze arc interactions and their influence on the gas shield flow. The shielding gases considered are pure argon and a mixture of argon with 18% CO 2. Comparison of the temperature fields predicted by the model with high-speed images indicates that the essential features of the interactions between the arcs are captured. The paper demonstrates strong arc deflection… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(9 citation statements)
references
References 29 publications
(39 reference statements)
0
9
0
Order By: Relevance
“…Though the model could be tested to be accurate enough in practice, it cannot consider more elements in reality and outputs were so limited, and other more characteristics were also required to be obtained. Schnick et al [30] developed a transient three-dimensional model of an anti-phase-synchronized tandem GMAW process using a professional software package ANSYS CFX to explore the arc behavior and gas quality during the process. This work modified the standard equations of computational fluid dynamic to take into account the electromagnetic and radiative phenomena that occur in thermal plasmas, and other relative equations.…”
Section: Numerical Simulation Of the Double-wire Gmaw Processmentioning
confidence: 99%
See 1 more Smart Citation
“…Though the model could be tested to be accurate enough in practice, it cannot consider more elements in reality and outputs were so limited, and other more characteristics were also required to be obtained. Schnick et al [30] developed a transient three-dimensional model of an anti-phase-synchronized tandem GMAW process using a professional software package ANSYS CFX to explore the arc behavior and gas quality during the process. This work modified the standard equations of computational fluid dynamic to take into account the electromagnetic and radiative phenomena that occur in thermal plasmas, and other relative equations.…”
Section: Numerical Simulation Of the Double-wire Gmaw Processmentioning
confidence: 99%
“…This work modified the standard equations of computational fluid dynamic to take into account the electromagnetic and radiative phenomena that occur in thermal plasmas, and other relative equations. The model used a mirror-symmetric geometry of the torch, parent and the fluid region (arc plasma), as shown in Figure .3 [30].…”
Section: Numerical Simulation Of the Double-wire Gmaw Processmentioning
confidence: 99%
“…In the almost-in-phase case, the time the trailing arc remains with intense deflection and low resistance to extinction is reduced; at the same time as the trailing arc resistance to extinction (interrup tion) is increased by raising its current level, its deflection is reduced. According to Schnick et al, minimizing arc deflection is crucial for efficient shielding of the welding region (arcs and welding pool) [11]. Again considering to the arc deflection model, an ideal situation, not tested in practice due to limitations in the control of the power sources, would be achieved for an in-phase situation, in which the trailing arc deflection would be kept at a low level all the time.…”
Section: Considerations On Arc Interruptions In Tandem Pulsed Gmawmentioning
confidence: 99%
“…Arc instabilities (abnormal arc voltages and interruptions) in Tandem Pulsed GMAW, also seem to play an important role in the introduction of air contaminations into the gas shield. Accord ing to a three-dimensional model of the Tandem GMAW arc welding process proposed by Schnick et al, the deflection (kink ing) of the arc in the base-current phase is particularly responsible for high levels of air contamination in the process region between the arcs and the hot regions of the workpiece, which might lead to weld seam imperfections such as porosity [11], Their model also demonstrates a strong deflection of the arcs during their basecurrent phases [11].…”
Section: Introductionmentioning
confidence: 99%
“…Ogino et al [11] conducted a numerical investigation on the tandem TIG arc plasma and weld pool formation, and found that the distance between welding wires obviously influenced the arc shape, and the maximum arc pressure of the twoelectrode TIG arc was much lower than that of a singleelectrode TIG. Schnick et al [12] presented a transient three-dimensional model of an anti-phase-synchronized pulsed tandem gas-metal arc welding process, which was used to analyze arc interactions and their influences on the gas shield flow. The results demonstrated that strong arc deflection and kinking occurred, especially during the low-current phase of the pulse, which was in agreement with experimental observations.…”
Section: Introductionmentioning
confidence: 99%